AB0845-HPR Impact of occupational therapy treatment in daily life activities dependence in a cohort of rheumatoid arthritis patients. (23rd January 2014) - Urbina, A.; Sandoval, C.; Beltran, D.; Villarreal, L.; Real, A. P.; Boon, P.; Palomino, A.; Bello, J.; Santos-Moreno, P.
Abstract : Background: Occupational Therapy's (OT) intervention has as a principal objective to get or to maintain independence and functionality in patients with Rheumatoid arthritis (RA). Independence in daily life activities (DLA) is the capability to perform every procedure in adequate time and without any help. RA is a disease that in most cases is associated with disability and loss of earning capacity; there is a lack of information about the of rheumatoid arthritis patients development after OT intervention in Colombia, being this field important in order to improve clinical and social outcomes for them. Objectives: The aim of this study was to describe the evolution of a cohort of RA patients underwent to six sessions of OT and its relationship with levels of independence in DLA at the first OT assessment and the final OT session, in a specialized in RA center in Colombia. Methods: A descriptive, cross sectional study was realized. A revision of medical records of a cohort of RA patients was performed, including occupational therapy records. Each patient was evaluated for OPHI – 2 (Occupational Performance History Interview 2), "Rodriguez y Arango" scale and total number of OT interventions. Independence in DLA were classified in: Independent (I), semi-independent (SI), semi-dependent (SD) and dependent (D), in relation with the speed and the need of external help required for performance. Each patient was underwent to six bimonthly sessions of OT as follows: at session 1 – OT assessment, at session 2 – energy savings techniques, at session 3 – joint prevention techniques in daily life activities, at session 4 – hand exercises, at session 5 - joint prevention techniques in procedimental activities, at session 6 – rehabilitation aids. Patients also were evaluated for DAS28, HAQ and OT parameters. Percentages and averages were calculated for demographic, clinical and occupational variables. The difference of medians was assessed using Chi-square test. Results: Of the 51 RA patients included, 12 (23.5%) were men and 39 (76.4%) women. Mean age 59.3 years, for women 59.2 and for men 59.4 years. At first session of OT, average DAS28 was 3.34 and average HAQ 0.13; at final OT session average DAS28 was 2.38 and average HAQ was 0.17. Regarding to independence in DLA, Patients were classified according to level of dependence in daily life activities development; at first OT evaluation 14 (27.4%) patients were I, 27 (52.9) were SI, 8 (15.7) were SD and 2 (3.9) were totally D. At final OT session 24 (47.06%) were I and 27 (52.94%) were SI; no patients in SD and D groups. The difference of medians was statistically significant for I and SI groups (p < 0.00), i.e. it was observed improvement in percentage of patients witch get independence or semi-independence in DLA. Conclusions: OT treatment improves independence in DLA in RA patients; Occupational Therapy's treatment generates progress in RA patient's dependence level in DLA and well-being. Disclosure of Interest: None Declared